(3OhQI RGO dJYdje GddZI GdYQHjI ddEjWGdjjf (B= Zad Lalingua Araba Per Gli Italianis ((3GdbGgQIs (3OGQ RGO ddfTQ hGdJhRjYs, 2009)
(3GdcJGH jbOe OhQI dJYdje GddZI GdYQHjI dfGWbi GdEjWGdjI HGSJNOGe GdWQb GdMOjKI eSMhHI HJSLjdGJ UhJjI ajSge ai JYde GdcdeGJ hGdLed GdCSGSjI hGdeMGOKGJ hbhGYO GddZI GdYQHjIs
(3eY (B: (3GdcJGH bQU edjRQs
(3GdfU HGddZJjf GdYQHjI hGdEjWGdjIs
Hurg
5 8
Keywords: (3GddZI GdYQHjIs -- (3GdbQGAIs; (3GddZI GdYQHjIs -- (3GdcJGHIs; (3GddZI GdYQHjIs -- (3CdaGXs; (3GddZI GdYQHjIs -- (3JYdje hOQGSIs; (3GddZI GdYQHjIs -- (3bhGYO GdEedGA hGdgLGAs